RENTABILITAS PERUSAHAAN AGRIBISNIS DI BURSA EFEK INDONESIA (BEI) - Eggidia Octafiani S; Leonardus Ricky Rengkung; Lyndon R. J. Pangemanan (AGRI-SOSIOEKONOMI, 2018)
This study aims to analyze the rentability of Agribusiness Companies on the Indonesia Stock Exchange (IDX). This research was conducted for 2 months from May to June 2018. The data used in this study is secondary data obtained from 3 companies, namely PT. Astra Agro Lestari Tbk (AALI), PPLondon Sumatra Tbk (LSIP) and PT Sawit Sumbermas Sarana Tbk (SSMS), the data collection has been reported to the Indonesia Stock Exchange (BEI) Manado City Branch. The results of the study show that PT. SSMS Tbk has a rentability that consists of ROA, ROE, GPM, NPM, which is higher than PT. AALI Tbk, and PT. LSIP Tbk. This means that PT SSMS gets the highest profit.*lrr+eprm*.